Process optimization, texture and microstructure of novel kelp tofu - Xianjiang Ye; Li Chen; Zhichen Su; Xiaojuan Lin; Jicheng Chen (Food Science and Human Wellness)
Laminaria japonica Aresch as an edible and medicine dual-purpose marine algae, has been gradually accepted by people. Tofu was Chinese traditional food, combining kelp function ingredients with tofu has practical value. The extraction-optimization methodology and the sequences of kelp antihypertensive peptide (KAP) were investigated. The sensory, whiteness, water retention ability (WRA) and microstructure of KAP tofu were evaluated. The scanning electron microscope (SEM) results showed KAP addition (20 %) significantly improved the tofu texture, with a denser network composed of relatively even pores. Compared with gypsum tofu and glucose-δ-interior fat (GDL) tofu, KAP tofu had significantly higher WRA (94.49 ± 0.49)% and sensory evaluation score value (92.54 ± 0.52), and a significantly lower IC50 value at (2.06 ± 0.04) mg/mL (P < 0.05). The maximum IC50 value (4.14 mg/mL) of kelp enzymatic hydrolysate was observed at enzyme (at an alkaline protease:trypsin ratio of 2:1) concentration 1.5 %, temperature 55 °C and time 2 h. The sequences of 8 identified peptides were Lys-Tyr, Phe-Tyr, Gly-Lys-Tyr, Ala-Lys-Tyr, Ser-Lys-Thr-Tyr, Lys-Lys-Phe-Tyr, Lys-Phe-Lys-Tyr and Ala-Lys-Tyr-Ser-Tyr with IC50 values of 5.24, 4.83, 7.94, 7.52, 20.63, 15.33, 10.73 and 2.42 μmol/L, respectively. These results indicated the potential use of KAP tofu as a valuable resource for development of functional foods.